An exploration of the way consumers use digital media of luxury fashion brands to create value: A case study analysis of Burberry - Bass, Chloe (2016)
This dissertation aimed to assess the effectiveness of Burberry’s digital marketing strategy at targeting millennials, whilst also investigating how and why its consumers create value via digital media. The study employed a mixed methods case study approach to data collection. During Phase I, 60 predominantly closed question surveys were conducted outside 2 key Burberry stores in order to gain insight into brand perceptions, luxury consumption and digital media habits. Five suitable candidates were then chosen to participate in Phase II; a semi-structured, follow-up interview. This provided contextual background by deepening understandings of the motives behind luxury consumption and digital media behaviour. Analysis of results showed that whilst there were some negative attitudes, the majority of millennials viewed Burberry as a successful and digitally-advanced luxury brand; thereby indicating it has achieved its aim. The importance of digital technology, particularly social media, was also made apparent in Phase II. The study found the use of technology increases interactions, thereby forms intimate and emotional relationships between Burberry and its consumers, and ultimately facilitates value co-creation. The overall findings of this study have supported, contradicted and extended existing knowledge within this field of research, however further investigations are required in order to improve the validity of conclusions. In particular, there is a clear gap in the literature on the use of digital media by luxury fashion brands in the value creation process; hence other brands should also be studied.